STUDI KUALITAS TELUR UDANG WINDU (Penaeus monodon Fabricius) PADA BALAI ATAU PANTI BENIH ASAL TAKALAR, MAROS, BARRU DAN MAJENE - Muhammad Syukri; Nurhikma Ramadhana (AgriSains, 2017)
Tiger shrimp (Penaeus monodon, Fabricius) is the most widely used shrimp in Indonesia as it is one of Indonesia's export commodities that meets about 70% of Japan's national needs, the United States and the European Union. The purpose of this study is to determine the quality of egg tiger shrimp include; levels of protein, fat, ash, water, and carotenoids found in several Seed Centers in South Sulawesi and West Sulawesi Provinces. The research took place in the districts of Takalar, Maros, Barru, and Majene. The parents of tiger shrimp that have reached fourth level gonad maturity (TKG IV) taken Tiger shrimp gonads to extract the eggs and then tested proksimat and the results are analyzed descriptively. The results showed that the quality of egg tiger shrimp from BPPBAP Maros is the best quality while the quality of eggs tiger shrimp comes from Seed halls and hatchery of DKP Majene Regency was the lowest quality eggs. Keywords : Egg Quality, Proximat Analysis, Comparison